2008
DOI: 10.1093/jxb/ern078
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ethylene biosynthetic and receptor genes in rose floral tissues during ethylene-enhanced flower opening

Abstract: Ethylene production, as well as the expression of ethylene biosynthetic (Rh-ACS1–4 and Rh-ACO1) and receptor (Rh-ETR1–5) genes, was determined in five different floral tissues (sepals, petals, stamens, gynoecia, and receptacles) of cut rose (Rosa hybrida cv. Samantha upon treatment with ethylene or the ethylene inhibitor 1-methylcyclopropene (1-MCP). Ethylene-enhanced ethylene production occurred only in gynoecia, petals, and receptacles, with gynoecia showing the greatest enhancement in the early stage of eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(59 citation statements)
references
References 43 publications
5
54
0
Order By: Relevance
“…Flowers were separated into five distinct parts: sepals, petals, stamens, gynoecia, and receptacles. Total RNA of sepals, petals, stamens, and receptacles was extracted using the hot borate method described by Ma et al (2005), and total RNA from gynoecia was extracted using the hot phenol method described by Xue et al (2008). We purified mRNA from total RNA using an Oligotex mRNA Purification Kit (Qiagen).…”
Section: Construction Of a Subtracted Cdna Librarymentioning
confidence: 99%
See 2 more Smart Citations
“…Flowers were separated into five distinct parts: sepals, petals, stamens, gynoecia, and receptacles. Total RNA of sepals, petals, stamens, and receptacles was extracted using the hot borate method described by Ma et al (2005), and total RNA from gynoecia was extracted using the hot phenol method described by Xue et al (2008). We purified mRNA from total RNA using an Oligotex mRNA Purification Kit (Qiagen).…”
Section: Construction Of a Subtracted Cdna Librarymentioning
confidence: 99%
“…Total RNAs were isolated from rose petals under the cyclic dehydration process as well as under control conditions following the procedures described by Xue et al (2008). cDNAs were synthesized from 1 mg of total RNA using Moloney murine leukemia virus reverse transcriptase (Promega).…”
Section: Semiquantitative Rt-pcr Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This confirmed that ethylene regulates flower opening of roses through signaling pathway and not through biosynthetic pathway. It 128 showed that ethylene enhanced both ethylene production and the expression of Rh-ACS2 or Rh-ACS3 in gynoecia, petals, and receptacles, with gynoecia showing the earliest ethylene enhancement. However, 1-MCP did not suppress ethylene production and the expression of the ethylene biosynthetic genes in these three tissues.…”
Section: -108mentioning
confidence: 99%
“…Ma et al (2005) while studying the differential induction features of three ACS genes in roses found that Rh-ACS2 is strongly induced by senescence. The tissue specificity of Rh-ACS2 has been found to be quickly induced by ethylene in gynoecia (Xue et al 2008). Similar observations have also been reported in carnation, where CARAS1 (also named as DCASC2) showed a quicker and stronger response to ethylene treatment in gynoecia than in petals (Have and woltering 1997).…”
Section: Genes Involved In Ethylene Synthesis (Acc Synthase and Acc Omentioning
confidence: 99%